DISTRIBUTION OF DIVIDENDS AND VALUE OF COMPANIES LISTED ON B3 - de Amorim, Gabriel; Lima, Nilton César; Brunozi Júnior, Antônio Carlos (Advances in Scientific and Applied Accounting, 2021)
Objective: Based on the trend of international stock markets, it is suggested that companies that do not distribute dividends are better valued by the market than companies that make a small distribution of profits, while companies with larger distributions of dividends are better valued. This scenario in the literature has been described as Relation in “J-Shaped”. In possession of this market aspect, this study aimed to identify whether there is the existence of the "J-Shaped" in the relationship between dividends and company value in the Brazilian capital market. Method: A sample of 3,556 observations of 271 companies, in the period 1996 to 2018, was divided into non-dividend-paying companies (DIV0) and dividend-paying companies, the latter being divided into five groups classified according to the dividend distributed (DIV1 to DIV5). The analysis of the format of the relationship was carried out through the medians of the groups and statistical tests to establish the statistical relationship between the distributed dividend and the firm value (Tobin's q). Results: It was found that the Brazilian market does not have the "J-Shaped". Thus, companies that do not pay dividends had worse values than those that distributed dividends to shareholders - with better valuations than those companies that distributed greater volumes of profits to stockholders. Additionally, the relevance of dividends in the value of companies in the Brazilian market was confirmed. Contributions: The work advances in the discussion of dividends and firm´s value in Brazil by proposing a new statistical approach to the subject, categorizing companies by their distinct profit distribution policies and highlighting the pro-dividend clientele in the Brazilian market.